Bayesian Estimation for Two Parameters of Gamma Distribution under Generalized Weighted Loss Function - Naji, Loaiy F.; Rasheed, Huda A. (Iraqi Journal of Science, 2019)
This paper deals with, Bayesian estimation of the parameters of Gamma distribution under Generalized Weighted loss function, based on Gamma and Exponential priors for the shape and scale parameters, respectively. Moment, Maximum likelihood estimators and Lindley’s approximation have been used effectively in Bayesian estimation. Based on Monte Carlo simulation method, those estimators are compared in terms of the mean squared errors (MSE’s).